Does status epilepticus induced at early postnatal period change excitability after cortical epileptic afterdischarges? - Mareš, Pavel; Kubová, Hana (Epilepsia, 2016)
Possible changes of cortical excitability after status epilepticus (SE) elicited in 12-day-old rats were studied by means of paired cortical afterdischarges (ADs). Consequences of lithium-pilocarpine status were studied in animals with implanted electrodes 3, 6, 9, 13, and 26 days after SE. Paired low-frequency stimulation with a 1-min interval was repeated after 10 min, and duration of ADs was measured. Control rats received saline instead of pilocarpine; other treatments were the same as in SE group. Postictal refractoriness (i.e., the testing response significantly shorter than the conditioning one) appeared at the age of 18 days in lithium-paraldehyde controls, whereas SE animals exhibited this phenomenon since postnatal day 21. The only significant difference between SE and lithium-paraldehyde controls was found in the second conditioning AD in the oldest group studied-it was longer in 38-day-old SE animals. Our results demonstrated moderate signs of higher excitability of SE rats in comparison with control ones long before appearance of spontaneous seizures.
Keywords: Cortical stimulation; Rats; Electroencephalography; Epileptic afterdischarges; Animals, Newborn; Status epilepticus; Ontogeny; Disease Models, Animal; Rats, Wistar; mužské pohlaví; elektroencefalografie; novorozená zvířata; krysa rodu Rattus; věkové faktory; Rat; Status Epilepticus; modely nemocí na zvířatech; mozková kůra; zvířata; Cerebral Cortex; status epilepticus; elektrická stimulace; Age Factors; potkani Wistar; Electric Stimulation; Male; Animals